Relationship Between Toe Clearance Strategy and Regional Regulation of Rectus Femoris Muscle During Swing Phase in Prolonged Walking in Young and Older Adults - Watanabe, Kohei (Frontiers in Physiology, 2018)
The toe clearance strategy during leg swinging while walking is closely associated with the risk of tripping and/or falling and is influenced by aging and a fall history. However, it remains unclear how the toe clearance strategy is regulated by the neuromuscular system. The present study investigated the effect of aging and fall history in the elderly on the toe clearance strategy and neuromuscular regulation of the rectus femoris (RF) muscle, which plays an important role in leg swinging, during prolonged walking. Thirteen elderly (age: 71.3±5.7 years) and nine young (age: 20.9 ± 0.8 years) men volunteered for the present study. The elderly subjects were divided into those with (n=6) and without (n=7) a fall history. Subjects walked on a treadmill at their preferred gait speed for 20 min, and lower extremity kinematics and multi-channel surface electromyography along the RF muscle were recorded. Variability of the minimum toe clearance (MTC) and central locus activation (CLA) of the RF muscle in elderly was significantly greater than in the young (p < 0.05). MTC significantly decreased with time in the elderly (p < 0.05), but not in the young (p > 0.05). There were no significant correlations between any parameters of MTC and CLA in the elderly or young (p > 0.05). MTC and variability of CLA significantly decreased with time in the elderly without a fall history (p < 0.05), but not in the elderly with such a history (p > 0.05). These results suggest that aging and a fall history in the elderly alter the toe clearance strategy and regional neural regulation of the RF muscle during prolonged walking.